Spindle cell angiosarcoma as primary cutaneous tumor - Case report and brief literature review - Tinca Andreea Cătălina; Lazar Bianca Andreea; Friciu Carmen; Cotoi Ovidiu Simion (Acta Marisiensis - Seria Medica)
Angiosarcoma is a rare, aggressive malignant tumor of vascular origin, often characterized by rapid growth and infiltrative behavior. While it commonly occurs in the skin, particularly on the scalp of elderly patients, it can also affect other regions. We present a case of a 76-year-old male with a rapidly growing, well-demarcated nodule on the dorsum of the hand, which was excised for pathological examination. Histopatho-logical analysis revealed spindle-shaped tumoral cells with a storiform pattern, poor vascularization, and immunohistochemistry positivity for CD31 and CD34. The case underscores the importance of distinguishing angiosarcoma from other spindle-cell tumors, such as leiomyosarcoma and atypical fibroxanthoma, and highlights the essential role of immunohistochemistry in achieving an accurate diagnosis. Early detection and appropriate surgical management are crucial for optimal outcomes in patients with this aggressive malignancy.